Using Hadamard transform for cryptanalysis of pseudo-random generators in stream ciphers - Sosa-Gómez, Guillermo; Rojas, Omar; Páez-Osuna, Octavio (EAI Endorsed Transactions on Energy Web, 2020)
In this work we discuss results obtained from an application of the Hadamard transform to cryptanalysis, and in particular, we determine the probability to decipher different pseudo-random number generators used as components of stream ciphers. Also, we found a relationship between entropy and Hadamard’s values.
Keywords: pseudo-random generators; Hadamard transform; stream ciphers; entropy